Induction Chemotherapy with Gemcitabine and Cisplatin Followed by Simultaneous Integrated Boost–Intensity Modulated Radiotherapy with Concurrent Gemcitabine for Locally Advanced Unresectable Pancreatic Cancer: Results from a Feasibility Study - Woo, Sang Myung (Cancer Res Treat, 2017)
PURPOSE: This study assessed the feasibility and compliance of induction chemotherapy with gemcitabine and cisplatin followed by simultaneous integrated boost–intensity modulated radiotherapy (SIB-IMRT) with concurrent gemcitabine in patients with locally advanced unresectable pancreatic cancer. MATERIALS AND METHODS: In this trial, patients received induction chemotherapy consisting of gemcitabine (1,000 mg/m(2)) and cisplatin (25 mg/m(2)) on days 1, 8, and 15 of each treatment cycle. Patients were subsequently treated with gemcitabine (300 mg/m(2)/wk) during SIB-IMRT. The patients received total doses of 55 and 44 Gy in 22 fractions to planning target volume 1 and 2, respectively. As an ancillary study, digital polymerase chain reaction was performed to screen for the seven most common mutations in codons 12 and 13 of the KRAS oncogene of circulating cell free DNA (cfDNA). RESULTS: Forty-four patients were enrolled between 2012 and 2015. Of these, 33 (75%) completed the treatment. The most common toxicities during induction chemotherapy were grades 3 and 4 neutropenia (18.2%), grade 3 nausea (6.8%) and vomiting (6.8%). The most common toxicities during SIB-IMRT were grade 3 neutropenia (24.2%) and grade 3 anemia (12.1%). Ten patients (23%) underwent a curative resection after therapy. Median overall survival was significantly longer in patients who underwent curative resection (16.8 months vs. 11 months, p < 0.01). The median cfDNA concentration was significantly lower after treatment (108.5 ng/mL vs. 18.4 ng/mL, p < 0.001). CONCLUSION: Induction chemotherapy with gemcitabine and cisplatin followed by concurrent SIB-IMRT was well tolerated and active.